Analisis Pengaruh Kualitas Produk, Citra Merek dan Kualitas Layanan terhadap Kepuasan Konsumen pada Pembelian Spare Part Merek BRT: Studi Kasus di Bengkel Hi-Standard Workhsop and Garage - Ismul Khobir; Lukitaningsih, Ambar; Tria Hatmanti Hutami, Lusia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to test whether Product Quality, Brand Image and Service Quality have an influence on Consumer Satisfaction in BRT brand spare part products. This study took samples from BRT brand spare part users. The method used in determining the sample is nonprobability sampling using the purposive sampling method. Data collection was carried out using questionnaires that were shared online through google forms. The number of respondent data processed was 130 people obtained based on the provisions of the Hair formula, namely the indicator multiplied by 8. The data of this study were analyzed using multiple linear analysis and this processing was carried out using SPSS version 26. The results of this study show that the Product Quality variable (X1), Brand Image variable (X2) and Service Quality variable (X3) have a simultaneous and partial effect on the Consumer Satisfaction variable (Y).